Preferential weld corrosion of X65 pipeline steel in flowing brines containing carbon dioxide - Alawadhi, Khaled; Robinson, M. J. (Maney, 2011)
The aim of this research was to investigate the cause of the severe localised corrosion that sometimes occurs at welds in carbon steel pipelines carrying hydrocarbons and inhibited brines saturated with carbon dioxide. A rotating cylinder electrode (RCE) apparatus was designed so that electrodes machined from the weld metal, heat affected zone (HAZ) and parent material of welded X65 pipeline steel could be galvanically coupled and tested in high shear stress conditions. The galvanic currents flowing between the weld regions were recorded using zero-resistance ammeters and their self-corrosion rates were found by polarisation resistance measurements. The total corrosion rate of each weld region was obtained from the sum of the self-corrosion and galvanic contributions. In uninhibited conditions, the weld metal and HAZ were both cathodic to the parent material and localised corrosion was prevented. However, when an oilfield corrosion inhibitor was present a current reversal took place, which resulted in accelerated weld corrosion. Electrochemical impedance spectroscopy (EIS) showed that the inhibitor film had lower electrical resistance and was less protective on the weld metal than on the parent material. At the highest shear stress, a second current reversal could occur when the inhibitor was removed from all regions of the weld and there was a return to the original galvanic behaviour. It was concluded that preferential weld corrosion was caused by unstable conditions in which the inhibitor film was selectively disrupted on the weld metal but remained effective on the other weld regions.